The Influence of Teacher Innovative Behavior, Principal Transformational Leadership and School Climate on High School Mathematics Teacher Performance - Andi Istiyawan; Zaenuri Mastur; Ari Tri Soegito; Heri Yanto (Universitas Negeri Semarang, 2022)
Abstrak. The problem in this study is to analyze the effect of teacher innovative behavior, principal transformational leadership, and school climate on the performance of high school mathematics teachers. This research was conducted using a quantitative approach. The population in this study were all high school mathematics teachers in Semarang City and Semarang Regency. In this study, one of the selected probability sampling techniques is simple random sampling. Data collection techniques were carried out by interview and observation, while the final stage was carried out using a questionnaire method. The data analysis technique was carried out by descriptive analysis and inferential analysis. The results of the study obtained descriptive data in the form of a profile picture of the respondents, besides that, a model developed based on theoretical studies and previous research was obtained. After conducting a confirmatory analysis of the research variables, the results showed that the indicators were able to reflect or explain the variables. Submission of SEM assumptions obtained normally distributed data, there is no outliers problem and there is no multicollinearity and singularity. The results of the full model hypothesis test indicate that this model is in accordance with the data or fits the data used in the study, and the conclusions obtained by the model are in accordance with the empirical data. The conclusion obtained from this research is that the higher the innovative behavior of the teacher and the transformational leadership of the principal, the higher the teacher's performance will be. On the other hand, school climate does not have a positive and significant effect on teacher performance.